EFEKTIFITAS PEMERIKSAAN KADAR GULA DARAH RUTIN TERHADAP PENCEGAHAN DIABETES MELLITUS TYPE II PADA IBU-IBU MULTIGRAVIDA - Juliandi; Nani Zulfikar (Poltekkes Kemenkes Medan, 2022)
Diabetes Mellitus (DM) is a disorder of carbohydrate, protein and fat metabolism characterized by hyperglycemia or an increase in blood glucose levels that occurs due to insulin secretion abnormalities or decreased insulin action (American Diabetes Association, 2012). The results of statistical analysis using t-test showed that the p-value was 0.323, meaning that there was no difference between the prevention of type II diabetes mellitus in the control group before and before treatment in multigravida mothers. While the intervention group before treatment was mostly ineffective, namely as many as 34 respondents (85%) after showing a very large change, most of them were classified as effective, namely as many as 32 respondents (80%), The results of the analysis using the t-test showed that the p-value the intervention group was 0.000, meaning that there was a difference between the prevention of type II diabetes mellitus in the intervention group before and before treatment in multigravida mothers.